2002
DOI: 10.1787/budget-v2-art6-en
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the waves of agencification and the governance problems they have raised in Central and Eastern European Countries

Abstract: The goal of this paper is to provide tools to understand and analyse waves of "agencification" in transition countries of Central and Eastern Europe. Agencification is a shorthand for the process of delegation and devolution, in which more autonomy, particularly in personnel and financial issues, is granted to public bodies, which either remain legally part of the state or acquire their own legal personality. It can also mean creating or moving functions to bodies, which are subsidiary or separate from ministr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 0 publications
1
16
0
1
Order By: Relevance
“…Therefore, it is generally concluded that the administrative changes in the first phase of transition can be expected to be driven most of all by the strategies of political elites with a central aim to overcome the legacy of the previous system (Hesse, 1997;Nemec, 2009). In terms of publicsector structure, the communist system left behind an institutionally fragmented administration with large numbers of ministries, central agencies, and specialized units (Beblavý, 2002;Goetz & Wollmann, 2001). At the same time, these organizations were not part of a centralized, horizontally and vertically well-integrated hierarchy, as is often presumed, but of an amorphous system that endured thanks to accommodating both the Communist Party's organizational and its members' and administrators' individual interests (Beblavý, 2002).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is generally concluded that the administrative changes in the first phase of transition can be expected to be driven most of all by the strategies of political elites with a central aim to overcome the legacy of the previous system (Hesse, 1997;Nemec, 2009). In terms of publicsector structure, the communist system left behind an institutionally fragmented administration with large numbers of ministries, central agencies, and specialized units (Beblavý, 2002;Goetz & Wollmann, 2001). At the same time, these organizations were not part of a centralized, horizontally and vertically well-integrated hierarchy, as is often presumed, but of an amorphous system that endured thanks to accommodating both the Communist Party's organizational and its members' and administrators' individual interests (Beblavý, 2002).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In terms of publicsector structure, the communist system left behind an institutionally fragmented administration with large numbers of ministries, central agencies, and specialized units (Beblavý, 2002;Goetz & Wollmann, 2001). At the same time, these organizations were not part of a centralized, horizontally and vertically well-integrated hierarchy, as is often presumed, but of an amorphous system that endured thanks to accommodating both the Communist Party's organizational and its members' and administrators' individual interests (Beblavý, 2002). There was no effective separation of powers, and the executive branch was characterized by considerable rulemaking capacities (Hesse, 1997).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Public agencies did in fact exist under communism and had a legal personality, often enjoying significant discretion in budget and personnel matters. The communist system also saw information asymmetry problems between legal entities and the centre, as well as a battle for policy control (Beblavý 2002a, p. 127).…”
Section: Agencies In Slovakiamentioning
confidence: 99%
“…If, at the same time, the number of “old” institutions is not cut, their total number is raised beyond a manageable limit which results in the non‐transparency of the entire central state administration’ (INEKO 2000, p. 6). According to Beblavý (2002a, p. 128), the agency model that emerged from communism was a ‘chaotic free‐for‐all, where organizations often have legally defined autonomy, rights and responsibilities, their staff and particularly managers feel certain informal ownership rights and the distinction between public‐and private‐sector mentality is blurred or non‐existent in the eyes of most actors’.…”
Section: Agencies In Slovakiamentioning
confidence: 99%
“…However, for the purposes of this analysis, we will stem from the above categorisation and consider companies fully owned by municipalities as "quasi in-house", within the framework of the "in-house" category. For more details on various forms of delivery and their use in transition countries see Beblavý (2002).…”
mentioning
confidence: 99%